Most frequent sanitary inadequacies in radiology services in the city of Salvador - BA: preliminary results (Research, Society and Development, 2020)
Introduction: Sanitary inadequacies have been frequently identified by control institutions, such as municipal health surveillance, in inspection activities in radiology services. Objective: To verify the factors associated with the occurrence of sanitary inadequacies in radiology services registered by the Sanitary Surveillance of the city of Salvador-BA, between 2013 and 2018. Material and method: A study was carried out with secondary data, collected in March and April 2019, based on records of health inspections in radiology services, carried out in the period from 2013 to 2018. Environmental variables, radiological protection, equipment / device / material conditions and the Quality Assurance Program (PGQ) were included. Results: The number of inadequacies it was 90 in the 21 inspected services that totaled the present sample was higher in 2018, in the months of January, March, July, and November, with greater polarization in one of the 3 districts studied. In environmental terms, there were 49 occurrences of infiltrations, 46 of dirt, and 34 of absence of easily cleaned walls and floors. Conclusion: The recurrence of sanitary inadequacies by the services studied raises the possibility of using the predictor variables as candidates for markers of sanitary inadequacies, if necessary, further studies with greater depth, for a better understanding of these findings.